PENDAMPINGAN KELOMPOK MASYARAKAT (BKR dan PIK-R) TANGGAP COVID-19 DALAM RANGKA PENCEGAHAN PENYEBARAN DAN PENULARAN VIRUS CORONA MELALUI POLA HIDUP SEHAT DI KELURAHAN BENDAN KERGON KOTA PEKALONGAN - Maslahatul Inayah; Yuniske Penyami; Hartati Hartati (Jurnal Lintas Pengabdian Masyarakat, 2021)
COVID-19 is declared a world pandemic by WHO and determined by the Government as a non-natural disaster in the form of disease outbreaks that need to take integrated countermeasures including the involvement of all components of society. In response to the current Covid-19 outbreak caused by the corona virus, the role and function of the family is the main basis for cutting the chain of corona virus transmission in the community. Breaking the chain of Covid-19 spread can be done by preventing and handling Covid-19 in the family. This is very important and useful so that we are able to maintain and prevent the spread of the virus in the family, as well as efforts to prepare ourselves for the Covid-19 outbreak.The purpose of this community service is to improve the quality of community groups such as BKR and PIK-R as response groups for Covid 19 so that they become models for other BKR and PIK-R groups in the Bendan Kergon Village area.This service method is carried out in a group of teenage family development (BKR) and a group of teenagers totaling 30 (thirty people). Activities carried out by conducting health outreach on preventing the spread and transmission of the corona virus as well as creative and innovative training activities (life skill education) such as the manufacture of processed dimpsum, fish burgers and dalgona drinks.The conclusion of the family is the main center in preventing the spread and transmission of Covid 19. Compliance with family members in preventing the spread and transmission of Covid 19 has played a major role in reducing the impact of the COVID-19 pandemic.Â Keywords: BKR and PIK-R groups, Covid-19, Healthy Living Behavior.